IMPROVING FAMILY RESILIENCE IN PRIMARY AND SECONDARY STROKE PREVENTION THROUGH LIFE'S ESSENTIAL 8-BASED INTERVENTION - Arisetijono, Eko; Yueniwati, Yuyun; Damayanti, Ria; Ernanda, Shelby Amrus; Savitri, Kania Aviandi; Romadhoni, Muhammad Rifqy; Taqiyyah, Masyalia Hasna; Haq, Nabiila Ala Qoonita Najma; Sinaga, Alexandra Maria Rossadwina Sriharkita; Alam, Satria Sabda; Zahra, Farah Shabri Alifia; Pranowo, Muhammad Royyan; Raihana, Naura Salwa; Siraj, Resnanda Naufal (MNJ (Malang Neurology Journal), 2026)
Background: Stroke is a leading cause of long-term disability in Indonesia, with rising incidence among individuals of productive age. Rural communities face multiple challenges, including low health literacy, high prevalence of risk factors, and persistent misconceptions about stroke prevention and post-stroke care. Objective: This study aimed to evaluate the effectiveness of a community-based intervention using the Life’s Essential 8 (LE8) framework and the SIGAP 8 pocket-book to strengthen family preparedness for primary and secondary stroke prevention in Besole Village, Tulungagung. Methods: A mixed-methods approach was applied in two phases: (1) pre-intervention assessment through demographic surveys, in-depth interviews, and FGDs with stakeholders to identify community needs; and (2) intervention through structured education, health screening, and pre–post knowledge testing. Participants underwent measurements of blood pressure, BMI, glucose, cholesterol, WHO stroke risk assessment, and Barthel Index evaluation for survivors. User experience of the SIGAP 8 booklet was assessed using the User Experience Questionnaire (UEQ). Results: A total of 34 stroke survivors and 21 non-stroke participants were included. Among survivors, 58.8 percent had stage 2 hypertension and 26.5 percent had glucose ≥200 mg/dL. Most demonstrated moderate dependence on the Barthel Index. Among non-stroke participants, 57.1 percent were classified as moderate risk. UEQ scores indicated positive user experience across dimensions, including dependability (3.82), attractiveness (3.69), and clarity (3.67). The LE8-based intervention effectively improved health literacy, motivation, and family capacity in monitoring stroke risk factors. Conclusion: The SIGAP 8 pocket-book was well-received and shows strong potential as a community-level tool for stroke prevention in rural areas.